1996
DOI: 10.1038/381520a0
|View full text |Cite
|
Sign up to set email alerts
|

Speed of processing in the human visual system

Abstract: How long does it take for the human visual system to process a complex natural image? Subjectively, recognition of familiar objects and scenes appears to be virtually instantaneous, but measuring this processing time experimentally has proved difficult. Behavioural measures such as reaction times can be used, but these include not only visual processing but also the time required for response execution. However, event-related potentials (ERPs) can sometimes reveal signs of neural processing well before the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

108
1,599
10
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 3,080 publications
(1,730 citation statements)
references
References 0 publications
108
1,599
10
13
Order By: Relevance
“…1e). This property of our encoding scheme is compatible with the impressive speed of processing found in the mammalian visual system (22).…”
Section: Resultssupporting
confidence: 70%
“…1e). This property of our encoding scheme is compatible with the impressive speed of processing found in the mammalian visual system (22).…”
Section: Resultssupporting
confidence: 70%
“…In other words, a low-level visual property, such as LSF, might provide the foundation for a high-level cognitive faculty, such as categorization. Indeed, event-related potentials studies (56,57) have repeatedly shown that humans can distinguish between the category of objects in scenes extremely rapidly, which we argue can be mediated by coarse LSF representations, and that this distinction is first apparent in prefrontal cortex time courses Ϸ150 ms from stimulus onset. That such prefrontal representations subsequently guide the activation of IT representations is supported by fMRI studies in human patients (9,58) and electrophysiology recordings in monkeys (10).…”
Section: Discussionmentioning
confidence: 69%
“…The preliminary processing that was unaltered by attention in our task may reflect a feed-forward phase of perceptual processing that precedes activity that is modulated by a more distributed neural system (2,29,30). Later responses show stronger modulation by effects that suggest top-down control, such as attention, priming, and familiarity (13,15,17,19,20).…”
Section: Discussionmentioning
confidence: 87%